2004
DOI: 10.1093/ndt/gfh139
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing C1q nephropathy from lupus nephritis

Abstract: The implications of a diagnosis of lupus are considerable, and we propose that the term 'seronegative lupus nephritis' is unhelpful, and should be avoided when there is diagnostic uncertainty. The term C1q nephropathy should be preferred when these histological features are seen in the absence of overt lupus, when C1q deposition is dominant and when tubuloreticular bodies are absent. The clinical course in the cases reported here does not support the use of immunosuppressive therapy in C1q nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
0
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 10 publications
5
42
0
11
Order By: Relevance
“…In 30.6%, a "full house" pattern, which is often observed in lupus nephritis, 11 was demonstrated significantly more frequently in patients with proliferative glomerulonephritis; however, none of our patients showed any feature of SLE at the time of biopsy or after a mean 5.4-yr follow-up, including six with endothelial tubuloreticular inclusions and two with extraglomerular small vessel vasculitis. Similarly to our results, Sharman et al 12 described nine patients who had C1q nephropathy and for whom a diagnosis of "seronegative lupus nephritis" had initially been considered. None of these patients developed SLE during a mean follow-up of 5.1 yr.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In 30.6%, a "full house" pattern, which is often observed in lupus nephritis, 11 was demonstrated significantly more frequently in patients with proliferative glomerulonephritis; however, none of our patients showed any feature of SLE at the time of biopsy or after a mean 5.4-yr follow-up, including six with endothelial tubuloreticular inclusions and two with extraglomerular small vessel vasculitis. Similarly to our results, Sharman et al 12 described nine patients who had C1q nephropathy and for whom a diagnosis of "seronegative lupus nephritis" had initially been considered. None of these patients developed SLE during a mean follow-up of 5.1 yr.…”
Section: Discussionsupporting
confidence: 89%
“…1,3,8,12 In our study, deposits were demonstrated in 90.6% of cases. We believe that occasional segmental distribution of immune deposits in C1q nephropathy may be the reason that they are not sampled for electron microscopy in some biopsies.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…C1q nephropathy is an uncommon pathological entity accounting for 0.4- 2.0% of all consecutive native kidney biopsies [5][6][7]. The distinguishing characteristics of C1q nephropathy are robust staining of C1q on immunofluorescence, absence of endothelial cell TRIs [8] and anti C1q antibodies [9]. Even though our index patient had C1q 2+ on IF, the presence of TRIs with sub endothelial deposits excludes C1q nephropathy.…”
Section: Discussionmentioning
confidence: 96%
“…Jones and Magil and Sharman et al reported such non-systemic mesangiopathic glomerulonephritis without progression to overt lupus nephritis [1,18]. Therefore, the term seronegative lupus nephritis is not useful.…”
Section: Discussionmentioning
confidence: 99%